Harrison's principles of internal medicine self-assessment and board review - Wiener, Charles M.; Brown, Cynthia D.; Hemnes, Anna R.; Longo, Dan L. 1949-; Harrison, Tinsley Randolph, 1900-1978 (New York, N.Y. : McGraw Hill Medical, 2017)
This is the companion review book to the most universally respected and read medical textbook in all of medicine. It features more than 1000 review questions, with complete answers and explanations - perfect for practice before IM certifying and recertification exams.
Hyperbaric and diving medicine -- Appendix: laboratory values of clinical importance -- Chapter e53 the clinical laboratory in modern health care -- Clinical procedure tutorials: introduction -- Chapter e54 clinical procedures tutorial: central venous catheter placement [video] -- Chapter e55 clinical procedures tutorial: thoracentesis [video] -- Chapter e56 clinical procedures tutorial: abdominal paracentesis [video] -- Chapter e57 clinical procedures tutorial: endotracheal intubation [video] -- Chapter e58 clinical procedures tutorial: phlebotomy [video] -- Chapter e59 clinical procedures tutorial: insertion of female urethral catheter [video] -- Chapter e60 clinical procedures tutorial: insertion of male urethral catheter [video] -- Chapter e61 clinical procedures tutorial: fine needle aspiration of breast cyst [video] -- Chapter e62 clinical procedures tutorial: iv insertion [video] -- Chapter e63 clinical procedures tutorial: fine needle aspiration of thyroid nodules [video] -- Chapter e64 clinical procedures tutorial: percutaneous arterial blood gas sampling [video] -- Chapter e65 clinical procedures tutorial: gynecologic examination with pap smear [video].
Includes bibliographical references and indexes.
Keywords: Internal medicine; Internal medicine